Postmenopausal vaginal atrophy: evaluation of treatment with local estrogen therapy - Minkin MJ; Maamari R; Reiter S (Dove Medical Press, 2014)
Mary Jane Minkin,1 Ricardo Maamari,2 Suzanne Reiter3 1Department of Gynecology and Reproductive Medicine, Yale University School of Medicine, New Haven, CT, USA; 2Novo Nordisk Inc., Plainsboro, NJ, USA; 3Mid-County Health Center, Largo, FL, USA Abstract: Postmenopausal vaginal atrophy, resulting from decreased estrogen production, frequently requires treatment. Estrogen preparations provide the most effective treatment; local application is preferred to systemic drugs when treating only vaginal symptoms. As local estrogen therapies have comparable efficacy, this study aimed to understand treatment practices, assess experiences with different forms of local estrogen-delivering applicators, and evaluate satisfaction. Women who were US residents aged ≥18 years, menopausal (no spontaneous menstrual period for ≥1 year or with a double oophorectomy), and receiving local estrogen therapy for 1–6 months (vaginal cream [supplied with a reusable applicator] or vaginal tablets [supplied with a single-use/disposable applicator]), completed an online questionnaire. Data from 200 women (100 cream users and 100 tablet users; mean therapy duration 3.48 months) showed that most stored medication in the room in which it was applied (88%) and applied it at bedtime (71%), a procedure for which cream users required, on average, more than twice the time of tablet users (5.08 minutes versus 2.48 minutes). Many cream users applied larger-than-prescribed amounts of cream, attempting to achieve greater efficacy (42%), or lower-than-recommended doses (45%), most frequently to avoid messiness (33%) or leakage (30%). More tablet users (69%) than cream users (14%) were "extremely satisfied" with their applicator. Postmenopausal women using local estrogen therapy were generally more satisfied with the application of vaginal tablets than cream. Patient satisfaction may help to facilitate accurate dosing. Positive perceptions of medication will help to optimize treatment, which, although not assessed in this study, is likely, in turn, to improve vaginal health. Keywords: local estrogen therapy, menopause, patient satisfaction, survey, vaginal atrophy